Determinants of Stunting among Children Aged 6-23 Months of Age in Pastoral Community, Afar Region, Ethiopia: Unmatched Case-Control Study - Mulaw, Getahun Fentaw; Adem, Omer Seid; Belachew, Abate Bekele (International Journal of Child Health and Nutrition, 2020)
Background: Globally, stunting is a public health concern, more of in developing counties, including Ethiopia. Once occurred, in the first two years of life, it is irreversible and has long-lasting harmful consequences. Exploring the determinants has pivotal importance for evidence-based interventions. Therefore, the rationale of this study was to identify determinants of stunting among children aged 6-23 months in the pastoralist community, Afar region, Ethiopia. Method: A community-based unmatched case-control study was conducted among 381 (cases=126, controls 255) study participants from February 15/2017 to March 30/2017. Cases and controls were identified consecutively using the world health organization growth monitoring chart. Data was collected by interviewer-administered questionnaires and anthropometric measurements. Statistical significance was declared at p-value < 0.05 in the final multivariable logistic regression model. Result: Maternal education (AOR:0.34, 95% CI: 0.16, 0.77), maternal under-nutrition (AOR:2.91, 95% CI:1.51, 5.60), number of under-five children within the household (AOR:2.66, 95% CI: 1.38, 5.10), latrine ownership (AOR:0.28, 95% CI:0.15, 0.55), minimum Dietary Diversity score of children (AOR:0.41, 95% CI:0.22, 0.75), child age (AOR:1.76, 95% CI:1.01, 3.09), colostrum intake (AOR:3.03, 95%CI:1.62, 5.66), and exclusively breastfeed for the first six months (AOR:3.20, 95% CI:1.72,5.95) were found to be determinants of stunting. Conclusion: This study found that determinants of childhood stunting are multifactorial. Maternal, household and child-related characteristics are associated with childhood stunting. Therefore, to improve childhood nutritional status, inter-sectoral collaboration and commitment are vital.